Mechanisms of low-temperature diffusion saturation of structural steel with nitrogen in the plasma of a low-pressure arc discharge; High Temperature Material Processes: An International Quarterly of High-Technology Plasma Processes; Vol. 17, № 4 - Ivanov Y. F.; Goncharenko I. M.; Grigoriev S. V.; Kolubaeva Y. A.; Schanin P. M.; Koval N. N. Nikolay Nikolaevich; Si-Ze Y. (2013, 2013)
The structure and the phase composition of the diffusion saturation zone of 40Cr- and 12Cr2Ni4N-type steels subjected to nitriding a low-pressure gas discharge plasma have been studied by the methods of optical, scanning, and diffraction electron microscopy. An essential possibility of nitriding steel at low (~200°C) temperatures has been revealed. The structural-phase state of the nitrided layer has been shown to depend strongly on the morphology and phase composition of the initial material.